PENGARUH MEDIA VIDIO PEMBELAJARAN TERHADAP HASIL BELAJAR MATA PELAJARAN PKN KELAS III DI SD ISLAM AL HIDAYAH SRENGSENG SAWAH - Alyaa Putri Nurchahyaningsih Alyaa; Arum Fatayan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to explore the influence of learning video media on learning outcomes for class III PKN subjects at Al Hidayah Islamic Elementary School, Srengseng Sawah. The method used in this research is Pre Experimental Design with a one group pretest-posttest research design type. The respondents for this research consisted of 30 class III students. Learning outcome data was collected through tests before and after treatment using learning video media. Data analysis was carried out by comparing test scores before and after treatment to see whether there were significant differences in learning outcomes after using learning video media. The results of this research indicate that the use of learning video media has a positive influence on learning outcomes for class III PKN subjects at Al Hidayah Islamic Elementary School, Srengseng Sawah. There is a significant increase in students' understanding and learning achievement after using learning video media. The use of learning video media can improve learning outcomes for class III PKN subjects at Al Hidayah Islamic Elementary School, Srengseng Sawah. Recommendations for future research are to involve more respondents and consider using stronger research methods, such as an experimental research design with a control group.